The miraculous of the Qur'an (Iʻjāz al-Qur'ān) and the Contemporary Science and Technology | إعجاز القرآن على العلوم والتكنولوجية المعاصرة - Al-Muhammadi Fauzan Masri (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2009)
This article tries to review the existing studies on the miraculous of the Qur'an as the greatest miracle of the prophet Muhammad. In this article, the writer concludes that the Qur'anic miraculous is over the development of contemporary science and technology. By employing philosophical approach and recent scientific data, the writer also reemphasizes the authenticity and authority of the Qur'an which was and still it is, and will remain as one of the most important miracles of the Prophet Muhammad.